STRUKTURALISME PILIHAN POLITIK PAGUYUBAN RESIK KUBUR JERO TENGAH - Ahmad Muttaqin (Jurnal Penelitian Agama, 2011)
Political choice is a normal phenomenon in a democratic system. However, it would be chaotic when it exists in a group that is socially awakened by mechanical solidarity. Individuality as a principle of democracy is pressed to obtain conformity. Political communalism normaliy happens in cultural groups such as Paguyuban Resik Kubur Jero Tengah, Kalikudi village, District Adipala, Cilacap. Through structuralism approach, solidarity and political choice becomes myth. In solidarity, political choice is projected to maintain harmony through the avoidance of taboos and the production of new values that are different from the habits that have taken place. As a myth, political choices concerning the structure of power have constantiy been established through a long historical process. The task of human being is to adjust the symptoms that occur with determinant historical Structures.